Biological variation of serum thyrotropin and thyroid hormones concentrations determined at 8‐week intervals for 1 year in clinically healthy cats - Prieto, Jennifer M.; Carney, Patrick C.; Smith, Stephanie M.; Miller, Meredith L.; Rishniw, Mark; Randolph, John F.; Salerno, Valerie J.; Lamb, Steve V.; Place, Ned J.; Farace, Giosi; Peterson, Sarah; Peterson, Mark E. (Veterinary clinical pathology, 2023)
Cats commonly develop thyroid disease but little is known about the long-term biological variability of serum thyroid hormone and thyrotropin (thyroid-stimulating hormone; TSH) concentrations. We aimed to determine the long-term biological variation of thyroid hormones and TSH in clinically healthy cats. A prospective, observational study was carried out. Serum samples for analysis of total thyroxine (T by radioimmunoassay [RIA] and homogenous enzyme immunoassay [EIA]), triiodothyronine (T ), free T (by dialysis), and TSH were obtained every 8 weeks for 1 year from 15 healthy cats, then frozen until single-batch analysis. Coefficients of variation (CV) within individual cats ( ) and among individual cats ( ), as well as the variation between duplicates (ie, analytical variation [ ]) were determined with restricted maximum likelihood estimation. The indices of individuality (IoI) and reference change values (RCVs) for each hormone were calculated. Some thyroid hormones showed similar (total T by EIA) or greater (TSH) interindividual relative to intraindividual variation resulting in intermediate to high IoI, consistent with previous studies evaluating the biological variation of these hormones weekly for 5-6 weeks. By contrast, total T (by RIA) and free T had a low IoI. Total T had a high ratio of to ; therefore, interindividual variation could not be distinguished from analytical variation. No seasonal variability in the hormones could be demonstrated. Clinicians might improve the diagnosis of feline thyroid disease by establishing baseline concentrations for analytes with intermediate-high IoI (total T TSH) for individual cats and applying RCVs to subsequent measurements.